Identification and Ranking of Motivational Factors Influencing the Tendency Toward a Health-Promoting Lifestyle in Women with Eating Disorders - Gorji Azandariyani, Hossein; Shakerinia, Iraj; Hosseinzadehmahdavi, Masoumeh (Psychology of Woman Journal, 2026)
Objective: This study aimed to identify and rank the key motivational factors that influence women with eating disorders in adopting and maintaining a health-promoting lifestyle.Methods and Materials: The research employed a sequential mixed-methods design consisting of a qualitative and a quantitative phase. In the qualitative phase, an extensive literature review was conducted until theoretical saturation was achieved to identify major motivational themes related to health-promoting behaviors in women with eating disorders. Qualitative data were analyzed using NVivo 14 software through open, axial, and selective coding, which resulted in seven main motivational categories. In the quantitative phase, the identified factors were operationalized into a structured questionnaire and administered to 200 women with eating disorders in Tehran. Participants were selected purposively from counseling and treatment centers. Data were analyzed using SPSS-26, applying descriptive statistics and mean-score ranking to determine the relative importance of each motivational factor.Findings: The results revealed that among the seven identified motivational dimensions, intrinsic motivation (M = 4.56) ranked highest, followed by emotional regulation (M = 4.47) and social support (M = 4.31). Cognitive awareness (M = 4.25) and environmental and cultural factors (M = 4.11) occupied intermediate ranks, while behavioral regulation (M = 4.02) and physical and health awareness (M = 3.89) ranked lower.Conclusion: Strengthening internal motivation, self-efficacy, and emotional regulation should be central to intervention programs aimed at sustainable behavioral change in this population.